A dromaeosaur from the Maastrichtian of James Ross Island and the Late - Case, J. A.; Martin, J. E.; Reguero, Marcelo Alfredo
The recovery of material of a small theropod from the Early Maastrichtian, Cape Lamb Member of the Snow Hill Island Formation is an unusual occurrence from primarily marine sediments. The pedal morphology of the specimen that includes a Metatarsal II with a lateral expansion caudal to Metatarsal III, a third metatarsal that is proximally narrow and distally wide, a Metatarsal III with a distal end that is incipiently ginglymoidal and a second pedal digit with sickle-like ungual are all diagnostic of a theropod that belongs to the family of predatory dinosaurs, the Dromaeosauridae. Yet this Antarctic dromaeosaur retains plesiomorphic features in its ankle and foot morphology. As new dromaeosaur species are being recovered from the mid-Cretaceous of South America and the retention of primitive characters in the Antarctic dromaeosaur, a new biogeographic hypothesis on dromaeosaur distribution has been generated. Gondwanan dromaeosaurs are not North America immigrants into South America and Antarctica; rather they are the relicts of a cosmopolitan dromaeosaur distribution, which has been separated by the vicariant break up of Pangea and created an endemic clade of dromaeosaurs in Gondwana. Fil: Case, J. A. Eastern Washington University; Estados Unidos Fil: Martin, J. E. South Dakota School of Mines & Technology; Estados Unidos Fil: Reguero, Marcelo Alfredo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina